Gang culture, Identity and Kaaps: Using Adam Small’s Krismis van Map Jacobs in Cape Flats schools - le Cordeur, Michael (Multilingual Margins: A journal of multilingualism from the periphery, 2018)
In this paper the focus is on the impact of gang culture on schoolchildren. The research question investigated here is whether teaching the drama Krismis van Map Jacobs offers any solutions to learners in gang-infested areas, given the framework of the Curriculum Assessment Policy Statement (CAPS). Two sub-questions considered whether the teaching of the drama should take place in Kaaps and whether the theme of Map Jacobs is still relevant within the CAPS curriculum 30 years after it was written by Adam Small. Theoretically, the paper is based on Pierre Boudieu's (1991) view that a speaker's 'position' in society determines whether he is heard, Bernstein's (1990) idea that social interaction influences your relationship with language and Vygotsky's (1978) theory of social constructivism. The study concludes that a life with gangs provides no solution for issues like poverty and unemployment, and that the youth should escape from a featureless existence through striving for good education and engaging with literature. The paper is published with the kind permission of the SA Academy for Science and the Arts, as it originally appeared in the book Adam Small: Denker, Digter, Dramaturg; 'n Huldingingsbundel (2017, SAWK).